The polymorphic state and real estate: rethinking the relationship between the state and real estate through Johannesburg & Bangalore - Pillay, Sarita (My University, 2022)
This research seeks to expand understanding of the relationship between the state and real estate. It is guided by the impulse, from experience in urban land justice activism, to acknowledge multiplicity in the state, and to contextualise the nebulous boundary between the private and public. I argue that commonly adopted concepts in critical scholarship – in the strands of urban power, urban planning and historical materialism – do not adequately offer a means to do this. Thus, drawing from how these concepts have been stretched and refuted in critical scholarship, an analytical lens is assembled for this research. It is guided by three influences: a historical materialist analytic of the urban; non-normative approaches to a postcolonial state theorised in India; and insights on the amorphous boundary between the state and private sector in real estate The starting point for this research is Johannesburg. However, an expansive spectrum of Indian critical scholarship surfaced in reading the relationship between the state and real estate. This raised the methodological utility of bringing Johannesburg into empirical conversation with an Indian city. Emerging organically as this city was Bangalore. Rather than ‘cases’, Johannesburg and Bangalore are approached as ‘vantage points’ through which to explore the relationship between the ubiquitous, albeit socially constructed, state and real estate. This research was thus guided by the question: (How) can the relationship between the state and real estate be conceptualised through Johannesburg and Bangalore? To begin to explore this, I undertook in-depth interviews with 62 key informants in real estate and government, as well as observations in real estate conferences and as an intern in a real estate consultancy firm. Additional analysis was undertaken of news articles, industry reports and building statistics. Three lesser-seen relationships between the state and real estate emerged, grounded in each city but developed through each other: an enabling relationship between local government and real estate shaped by the post-apartheid transition in Johannesburg; central government’s incorporation of real estate in Bangalore; and the Government Employees Pension Fund’s (GEPF) embeddedness in Johannesburg real estate as an ‘investor state’. In a landscape of differentiated real estate, the state was shown to be central to financialised forms of real estate – but not only so. This contributes to conceptualising a polymorphic state and real estate. Empirically, this work expands critical scholarship to direct considered attention to non-corporate forms of real estate in India, and listed corporate real estate in South Afric
A thesis submitted in fulfilment of the requirement for the degree Doctor of Philosophy to the Faculty of Engineering and the Built Environment, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2022